2016
DOI: 10.1080/02602938.2016.1221052
|View full text |Cite
|
Sign up to set email alerts
|

Is peer review an appropriate form of assessment in a MOOC? Student participation and performance in formative peer review

Abstract: Many aspects of traditional higher education must be reconceptualised for massive open online courses (MOOCs). Formative and summative assessment of qualitative work in particular requires novel approaches to cope with the numbers involved. Peer review has been proposed as one solution, and has been widely adopted by major MOOC providers but there is currently little evidence about whether it is appropriate in the MOOC context, or under what conditions. Here, we examine student participation, performance and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 29 publications
3
62
0
2
Order By: Relevance
“…ST2 concluded that "MOOC courses will not terminate universities' learning, but it is one way to support us to gain more knowledge". This finding is consistent with Al-Atabi and DeBoer (2014) and Meek et al (2017) who think that hybrid learning offers more opportunity to support students' learning and achievement.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…ST2 concluded that "MOOC courses will not terminate universities' learning, but it is one way to support us to gain more knowledge". This finding is consistent with Al-Atabi and DeBoer (2014) and Meek et al (2017) who think that hybrid learning offers more opportunity to support students' learning and achievement.…”
Section: Resultssupporting
confidence: 91%
“…This researcher found that 90% of his students completed the activities related to his course, and they were very positive about the method of teaching the course. Meek et al (2017) concluded that when mixing a MOOC with a traditional one, their results showed that students' performance in the written topic summary correlated with higher participation of students in the integral peer review task. Similarly, Griffiths et al (2014, p. 4) reported that, "students in the hybrid sections did as well or slightly better than students in the traditional sections in terms of pass rates and learning assessments".…”
Section: Introductionmentioning
confidence: 99%
“…Agreed good practice and guidelines for peer review would help to make this more effective (O'Toole, 2013). For example, when designing peer review, there could be options for differentiated support or peer groups for students with different ability levels, and opportunities to improve peer review skills (Meek, Blakemore, & Marks, 2016).…”
Section: Offer Well-designed Assessment and Accreditationmentioning
confidence: 99%
“…A concern that is reflected in the proposal of assessment approaches that target more reliability and more validity, combined with the objective of ensuring effective feedback to learners [5].…”
Section: Introductionmentioning
confidence: 99%
“…The openness of MOOCs implies dealing with enrolled learners who are not true peers, because of their different backgrounds, abilities, objectives, and behavior patterns [5].…”
Section: Introductionmentioning
confidence: 99%